Family Character and the Sustainability of Family-owned Businesses: A Focus on the Nigerian Education Sector - Emmanuel E. OKOH; Rowland E. WORLU; Olabode A. OYEWUNMI; Daniel E. UFUA; Olusola J. OLUJOBI (Communications of International Proceedings, 2021)
This study examined the effect of  owners of family-owned primary and secondary schools insistence of total control of the ownership and management (that is, family character) of the business. This research adopted a qualitative approach and applied the stewardship theory, which is often used in the literature on corporate governance and practice. It also relied on extant literature to explore the trend of thoughts about the critical features of family character on the concept of family-owned business sustainability in the Nigerian educational sector. The study found that many families do not have  adequate internal supply of professionals skills needed to facilitate the sustainability of family-owned enterprises in the education sector. This paper, therefore, advocates for a balanced ownership and management structure that allows professionals to be engaged, to bridge the gap of insufficient supply of expertise in the family, as this can better enhance family-owned business sustainability in the education sector.
Keywords: Family Character; Family-owned Businesses; Management; Ownership; Sustainability.